To buckle or not to buckle - Schwarz, Ulrich S. (Nature materials, 2020)
Epithelial layers under compression avoid buckling by active contraction, but only up to a well-defined threshold at 35% strain, beyond which buckling occurs.
Published online: 18 December 2019
Gesehen am 25.02.2020